Trust and electronic word of mouth on purchase intention: Rating as mediator - Kojongian, Keren Sonia Petronela; Ariadi, Gede (Universitas Ahmad Dahlan, 2024)
In an increasingly digital era, trust factors, electronic word of mouth, and ratings have an important role in influencing consumer purchase intention. This study examines the effect of trust and electronic word of mouth, with ratings acting as a mediator, on the purchasing intentions of health products. The research centers on Shopee users residing in Salatiga City during COVID-19. The study sample consisted of 103 inhabitants of Salatiga City who used the Shopee marketplace. The analysis was performed using the partial least-squares structural equation method. The results suggest that trust does not significantly impact purchase intent, but the trust variable has a positive and significant impact on ratings. Moreover, purchase intent was positively and significantly affected by the rating variable. Purchase intention and evaluations are positively and significantly affected by electronic word of mouth elements. It is clear that using ratings as mediators to link trust andpurchase intention has a significant impact. In contrast, the link between electronic word of mouth and purchase intention, where rating serves as a mediator, does not indicate any significant impact.